PENERAPAN STUDENT CENTRE LEARNING DENGAN METODE CONTEXTUAL INSTRUCTION DAN SMALL DISCUSSION GROUP PADA PEMBELAJARAN MANAJEMEN KEUANGAN - Sri Lestari; Intan Shaferi (JBIMA (Jurnal Bisnis dan Manajemen), 2014)
Student center learning getting relevant with current learning. Student center learning method can be applied variously. Among them, there are contextual instruction and small discussion group that is applied on financial management college on economic faculty.Financial management is attended by student in second semester. This lesson content both theoris and computation. Then, both contextual instruction and small discussion group is a suitable collaboration method.Contextual instruction focuses on cognitive implement at day-to-day life. Some ways did by video rotating, problem solving, individual and group assignation.Small discussion is a group from one class of college student, devided into some small groups that consist of 5 until 7 person to be an effective group discussion. Then, they were given illustration problem or specific topic to be discussed. Lecturer as facilitator will conduct and control the discussion.Both of that method matched to be done all together. Students satisfied with that method, and get good mark. Evaluation is done by giving the student quesionair for better learning.